La alternancia de las preposiciones "en"/ "a" en verbos de movimiento que denotan penetración en el español de México - Eslava Heredia, Cristina (El Colegio de México, 2012)
The goal of this paper is to analyze the alternative between the Spanishprepositions en/a in constructions with motion verbs that denotepenetration of a location (entrar, ingresar, etc.) This alternative marksa different way to conceptualize the action, as a result of the conceptualizationof locative entities (container vs. no container). The choiceof preposition triggers other semantic interpretations where mechanismssuch as metonymy play an important role.